FAKTOR- FAKTOR PENYEBAB DAN AKIBAT TINDAK PIDANA KORUPSI DITINJAU BERDASARKAN UU NO 20 TAHUN 2001 PERUBAHAN ATAS UU NO 31 TAHUN 1999 TENTANG TINDAK PIDANA KORUPSI (Studi Kasus di Kota Medan) - Maslon Hutabalian (Universitas Quality, 2019)
Crime of corruption is a social phenomenon which is the reality of human behavior in social interactions that are deemed to be deviant, things that are already commonplace, are no longer even common knowledge in the midst of the lives of nations and countries in particular, even throughout the world in general. In the country of Indonesia itself since the days of independence this has become an activity that is attached to stakeholders in the government body in particular, so that when talking about corruption is not a new thing anymore. But along with the times, that this seems to be an unstoppable culture, so it really needs serious attention for the government in terms of eradication. Considering that corruption is a despicable act, it is necessary to see and know what are the causal factors and the consequences of criminal acts of corruption on development in the city of Medan reviewed based on Law No. 20 of 2001 amendment to Law No. 31 Year 1999 concerning corruption. Therefore the author conducted a study in the Medan corruption court which was formed on May 28, 2011 ago.